Patterns, Trends, And Gaps In The Current Pool Of Knowledge, Thus Contributing To A More Diverse Understanding Of PBL In The Context Of Secondary Education - Judijanto, Loso (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2021)
This study aims to explore the past. It investigates the complex terrain of global learning initiatives and the development of cultural competencies in education. This research navigates the diverse aspects of this educational mosaic, examining the dynamic interplay between initiatives aimed at global learning and the development of cultural competencies. This study recognizes the important role of cultural competence in preparing learners for an interconnected world. This research method is qualitative with descriptive analysis. Through a comprehensive approach, this research opens up narratives that examine the various dimensions of advancing global learning initiatives, emphasizing their transformative impact. The results of this study examining educational paradigms underscore the evolving nature of pedagogy in response to the demands of an interconnected world. This retrospective study aims to contribute valuable insights into the symbiotic relationship between global learning and cultural competence, elucidating effective strategies for fostering a globally aware and culturally competent educational environment.